Generalitat de Catalunya : obra de govern 1931-1939 / Francesc Bonamusa (dir.) ; Josep M. Bricall ... [et al.] - Bonamusa Gaspá, FrancescBricall, Josep Maria (Referents; 1)
Contiene: Vol. I -- Vol. II